A Shiloh Christmas - Naylor, Phyllis Reynolds (Naylor, Phyllis Reynolds. Shiloh., 2015)
"Marty and his best friend, Shiloh are on another adventure. Marty learns when a secret is too dangerous to keep, and that hate can spread like fire"--